Mapping of Peak Ground Acceleration(PGA) using The Kawashumi Model for Sumatera - Tati Zera; Tati Zera (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
The position of the west coast of the island of Sumatra, which is the meeting point of the Eurasian and Indo-Australian plates, has high seismicity due to its tectonic activity. This high level of seismicity indicates that many earthquakes have an effect on ground motion. This study calculates and analyzes the maximum ground motion acceleration (Peak Ground Acceleration - PGA) as the effect of destructive earthquakes in Sumatra for 100 years from January 1, 1920 - December 31, 2020, based on the Kawashumi model. The calculation results give PGA values in the range of 388,190 – 4008,210 gal with a maximum value of 4199.45 gals at 3,295oN, 95,982oE caused by the 9.1 M earthquake on Andaman Island on December 24, 2004. While the minimum PGA value is 314.9 gals located at 4.438oLS - 101.367oBT caused by the Bengkulu 8.4 M earthquake. This calculation results in a map showing a high PGA pattern in the northern part of Sumatra and decreasing towards the south. This shows that destructive earthquakes that occur in the northern part of Sumatra Island pose a greater risk of ground movement compared to destructive earthquakes that occur in the southern part of Sumatra Island. This PGA pattern is different from several previous studies